2017
DOI: 10.1097/coh.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated malignancies in sub-Saharan Africa

Abstract: Purpose of review Summarize recent developments for HIV-associated malignancies (HIVAM) in low- and middle-income countries (LMIC) with particular focus on sub-Saharan Africa (SSA). Recent findings Antiretroviral therapy (ART) scale-up is leading to epidemiologic transitions in LMIC similar to high-income countries, with aging and growth of HIV-infected populations, declining infectious deaths, increasing cancer deaths, and transitions from AIDS-defining cancers (ADC) to non-AIDS defining cancers (NADC). Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 51 publications
(51 reference statements)
1
41
0
Order By: Relevance
“…This is in part because of the persistent viral replication and repeated stimulation of HIV-specific T cells that gradually drive these cells to senescence, characterized by exhaustion of their replicative capacity and even resulting in the loss of certain anti-HIV T cell clones (reviewed in [2]). Depending on the timing of ART initiation, some of these processes are not prevented, and in spite of low viral loads and normal CD4 + T cell counts, young individuals experience aging-related immune complications [3]. One study reported that HIV-infected persons on ART with a median age of 56 years, robust immune reconstitution and viral suppression had T cell characteristics similar to those of a group of HIV-uninfected subjects with a median age of 88 years (reviewed in [4]).…”
Section: Introductionmentioning
confidence: 99%
“…This is in part because of the persistent viral replication and repeated stimulation of HIV-specific T cells that gradually drive these cells to senescence, characterized by exhaustion of their replicative capacity and even resulting in the loss of certain anti-HIV T cell clones (reviewed in [2]). Depending on the timing of ART initiation, some of these processes are not prevented, and in spite of low viral loads and normal CD4 + T cell counts, young individuals experience aging-related immune complications [3]. One study reported that HIV-infected persons on ART with a median age of 56 years, robust immune reconstitution and viral suppression had T cell characteristics similar to those of a group of HIV-uninfected subjects with a median age of 88 years (reviewed in [4]).…”
Section: Introductionmentioning
confidence: 99%
“…The finding that patient-reported HIV was significantly associated with provider-referral at first CCS is particularly important since several studies have found that HIV infected women are at greater risk of developing precancer and ICC [ 21 , 30 34 ]. Because of this risk, studies have demonstrated the critical role of health care providers in linking HIV infected women to important reproductive health services including CCS in areas with a high HIV burden [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many areas of Africa affected by the HIV epidemic, HIV-associated malignancies are among the most common cancers in the overall population [1]. For example, despite growing availability of antiretroviral therapy (ART), Kaposi's sarcoma (KS), as of 2018, remains the most incident cancer in many parts of eastern and southeastern Africa, including Malawi, Mozambique, Uganda, and Zambia [2].…”
Section: Introductionmentioning
confidence: 99%